IDENTIFIKASI CURRENT & NEEDED CORE COMPETENCIES PTS X - Dewi, Ratnasari; Wiratmadja, Iwan Inrawan; Arijanto, Sugih (REKA INTEGRA, 2014)
Walaupun PTS X telah memiliki beberapa landasan yang dapat mendukung tercapainya visi dan misi, diantaranya Rencana Strategis (Renstra) dan Rencana Induk Pengembangan (RIP). Namun PTS X belum mengidentifikasi core competence, pencapaian visi dan misi akan lebih mudah dicapai ataupun sempurna dalam pencapaiannya, jika memiliki core competence (kompetensi inti). Core competencies (kompetensi inti) adalah kapabilitas perusahaan yang mendasar dan berperan dalam membentuk keunggulan bersaing serta pusat dari formulasi strategi untuk memenuhi visi dan misi dalam memberikan keuntungan di pasar atau lingkup pelayanan. Terdapat dua kompetesi yang diidentifikasi yakni current core competence dan future core competence. Current core competence yang telah dimiliki adalah kepedulian dosen terhadap mahasiswa, dan future core competence yang harus dimiliki adalah support. Kata kunci: strategi bersaing, kompetensi inti, perencanaan strategis ABSTRACT Although PTS X has had some foundation that can support the achievement of the vision and mission, including the Strategic Plan (Strategic Plan) and Development Master Plan. However, PTS X has not been identified core competence, vision and mission will be more easily achieved nor perfect in its achievements, if it has a core competence (core competencies). Core competencies (core competence) is a fundamental capability of the company and was instrumental in establishing a competitive advantage as well as the center of formulation strategies to fulfill the vision and mission in providing advantages in the market or scope of services. There are two identified competencies ie, current and future core competence, core competence. Current core competence is a concern that has been owned by the lecturer to the students, the future core competence is a must-have support. Keywords: competitive strategy, core competencies, strategic planning